Tubular Duplication of the Midgut Presenting with Acute Abdomen and Hematochezia: A Case Report from Northern Tanzania. (24th January 2018) - Herman, Ayesiga M.; Msuya, David; Kaino, Mwemezi; Shilanaiman, Hilary; Magoma, Joachim; Issangya, Christian; Lodhia, Jay; Tarmohamed, Murad; Pyuza, Jeremia; Amsi, Patric; Mremi, Alex; Mbwasi, Ronald; et al.
Abstract : Enteric duplication is one of the rare malformations affecting the small intestine more than the other parts of the gastrointestinal tract. It poses a challenge in diagnosis due to nonspecific symptoms that may mimic other pathologies. Furthermore, the management options including total resection, mucosal striping, and internal drainage of the duplicate depend on the presentation of the patient, site, and length of the involved bowel. We present the first documented case of enteric duplication in Tanzania, a 3-year-old male, who was found to have a 90 cm long jejunoileal duplicate. We discuss the presentation and management offered.